The Hedonic and Eudaimonic Motives for Activities: Measurement Invariance and Psychometric Properties in an Adult Japanese Sample - Asano, Ryosuke; Igarashi, Tasuku; Tsukamoto, Saori (Frontiers in Psychology, 2020)
Hedonic pleasure orientation (seeking enjoyment), hedonic relaxation orientation (seeking comfort), and eudaimonic orientation (seeking meaning) are major ways that people pursue well-being. We investigated the measurement invariance and psychometric properties of the Hedonic and Eudamonic Motives for Activities (HEMA) scale in a Japanese adult sample (N = 1,892). The Japanese HEMA scale demonstrated measurement invariance at the configural, metric, scalar, and strict levels across gender and age groups. Latent mean differences of the scale across these demographic groups were less than small. The scale showed high internal consistency and six-week test-retest reliability and reasonable correlations with life satisfaction, positive affect, negative affect, psychological well-being, and interdependent happiness. In sum, these findings suggest that the Japanese HEMA scale is useful to capture hedonic and eudaimonic conceptions of well-being as orientations. It is hoped that our findings will stimulate further research on well-being using the HEMA scale.